Optimization of Rate of Penetration and Mechanical Specific Energy Using Response Surface Methodology and Multi-Objective Optimization - Mantegazini, Diunay Zuliani [UNESP]; Nascimento, Andreas [UNESP]; Mathias, Mauro Hugo [UNESP]; Romero Guzman, Oldrich Joel; Reich, Matthias (My University, 2025)
Optimizing the drilling process is critical for the exploration of natural resources. However, there are several mechanic parameters that continuously interact with formation properties, hindering the optimization process. Rate of penetration (ROP) and mechanical specific energy (MSE) are considered two key performance indicators that allow the identification of ideal conditions to enhance the drilling process. Thus, the goal of this research was to analyze field data from pre-salt layer operations, using a 2D analysis of parameters as a function of depth, response surface methodology (RSM), and multi-objective optimization. The results show that the RSM method and multi-objective optimization provide better results when compared with 2D analysis of parameters as a function of depth. The RSM method can be used as a tool to analyze the effects of the independent drilling mechanical parameters (WOB, RPM, FLOW, and TOR) on the response variables (ROP and MSE) with a 95% confidence level. Through multi-objective optimization, it was possible to concomitantly achieve an ROP of approximately 22 ft/h and MSE of nearly 11 kpsi using the values of WOB, RPM, FLOW, and TOR of about 11 klb, 109 rev/min, 803 gpm, and 3 klb-ft, respectively. Using high WOB values, i.e., from the mean value up to the maximum value of approximately 43 klb, reflects a low ROP and most likely indicates an operation beyond the foundering point. High FLOW promotes a more efficient hole cleaning and higher rates of cuttings transport, thus preventing eventual in situ drill-bit sticking. Flow adjustment also ensures an adequate balance of dynamic bottom hole pressure, in addition to controlling the force impact force of the drilling fluid in contact with the rock being drilled, expressing importance in terms of efficiency and rock penetration. Finally, it is important to mention that the results of this research are not only applicable to hydrocarbon exploration but also to geothermal and natural hydrogen exploration. Values analyzed and presented with decimal precision should be logically focused as integers when in industrial application.
Keywords: carbonate rock; drilling; efficiency; natural resources; optimization